Can a Good Break Shot Determine the Game Outcome in 9-Ball? - Pan, Jing Wen; Komar, John; Sng, Shawn Bing Kai; Kong, Pui Wah (Frontiers in Psychology, 2021)
This study aimed to quantify the break shot characteristics and identify their significance in predicting the game outcomes in 9-ball tournaments. The break shot of 275 frames (241 men’s, 34 women’s) of professional tournaments were analyzed from two aspects: 1) cue ball position, represented by the distance between the cue ball and the table center, and 2) ball distribution, indicated by the standard deviation of Voronoi cell areas determined from all remaining balls on the table. Spearman correlation and binary logistic regression were utilized to identify associations and to predict the frame outcomes, respectively. Results showed that the more balls falling into the pockets during the break, the more clustered the remaining balls (rs = 0.232, p < 0.001). The closer the cue ball ending towards the table center, the more balls potted in the visit immediately after the break (rs = -0.144, p = 0.027). Neither cue ball position nor ball distribution could predict table clearance or winning of a frame. In conclusion, pocketing more balls during the break is associated with more clustered balls remaining on the table. Parking the cue ball near the table center after the break can facilitate potting more balls immediately after.